Molecular survey and genetic diversity of hemoplasmas in rodents from Chile - Alabí, Amir Salvador; Monti, Gustavo; Otth, Carola; Sepulveda-García, Paulina; Sánchez-Hidalgo, Melissa; de Mello, Victória Valente Califre [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; Bittencourt, Pedro; Müller, Ananda (MDPI, 2020)
Even though hemotrophic mycoplasma (hemoplasma) infections are well documented in a wide variety of hosts worldwide, there is a gap in the knowledge aobut hemoplasmas in rodents. This study aimed to molecularly survey and investigate the genetic diversity of hemoplasmas in rodents from Chile. Synanthropic and wild rodents (n = 74) were captured in the southern province of Valdivia (Corral, Valdivia, Riñihue, and Reumén localities). Spleen samples were submitted to a conventional PCR for hemotrophic Mycoplasma spp. targeting the 16S rRNA gene (800 bp), followed by sequencing, phylogenetic, and genetic diversity analyses. The overall occurrence of hemotrophic mycoplasmas in rodents from Valdivia was 24.5% (18/74) [95% CI (14.5; 34.1)]. Hemoplasmas were detected in Mus musculus (1/4), Rattus norvegicus (1/16), Abrothrix longipilis (7/13), A. olivaceo (6/8), and Oligoryzomys longicaudatus (3/10). The nucleotide polymorphism analysis of the targeted 16S rRNA region showed low diversity, with two genotypes and a high identity to the variants detected in wild rodents from Brazil. Hemoplasmas are described for the first time in rodents from Chile with a moderate occurrence and low 16S rDNA genetic diversity within the sampled rodent population. The detected hemoplasma genotypes were specific to rodents and were not shared with other mammals.
Keywords: 16S rRNA; Hemotrophic mycoplasmas; Rodentia; South America